Techniques of satirical writing in the African novel - Southern Sahara -: Fredinand Ayounou’s “A boy’s life” as an example - Sekmakdji, Iskander (Journal of Human Sciences, 2022)
The modern African novel – Southern Sahara- can be included among narrative representations of the post-colonial studies. This modern form of the novel has been established since the era of the general human emancipation seeking freedom from social slavery. African novelists benefited in this context from satire as one pillar of novel creation. Thus, the African novelist tried satirical expressions to recover confidence in himself, incite for action and break fear. The present paper presents, on one hand, a methodological comparative approach to the African narrative text, as a marking aesthetic sign through the use of such linguistic means, and a minute description of the African image, on the other hand; depicting satirical and ironical forms. This is revealed in Ferdinand Oyono’s novel “A boy’s life” who made use of satire as an artistic aesthetic tool capable of highlighting the contradiction in the African social structure governed by segregation rules and customs dictated by the while.